Controversies in Formative Shiʿi Islam - Sajjad Rizvi (International Institute of Islamic Thought, 2017)
Research into the formative period of Shiʿi Islam has come a long way in the last couple of decades. This welcome development has been inspired, in particular, by the work of Mohammad Ali Amir-Moezzi, whose main insight has been to posit that “ancient” Shiʿism is marked precisely by those doctrines and positions that the later rationalizing tradition rejected as “extreme” (ghulūw). This particular form of heretication and othering made sense once the communities had been established; were seeking official recognition by the Abbasid and other royal courts; and developed the institutions of learning, as well as structures and hierarchies, visible in other Muslim confessions. Nevertheless, there remained the questions of what made Shiʿi Islam distinct, how one could differentiate among those tendencies that defined themselves as Shiʿi, and what sort of construction was “extremism” (I recognize that this is a highly inadequate rendition of ghulūw). Amir-Moezzi’s contribution is further complicated by Hossein Modarressi’s groundbreaking study of the formative period during the early 1990s, in which he posited that ghulūw was exterior to the circle of the Imams and perceived as a constant contrast and threat to the moderation of the scholarly community that remains to this day ...